2013
DOI: 10.1007/s10286-013-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

Unaltered R–R interval variability and bradycardia in cyclists as compared with non-athletes

Abstract: Bradycardia and higher oxygen uptake were found in association with unaltered cardiac autonomic modulation in elite mountain bikers athletes in supine and orthostatic positions, compared to active non-athletes. This bradycardia was not dependent on distinctive resting autonomic modulation. Intrinsic adaptation of sinus node and/or a peculiar state of autonomic adaptation to this exercise can be possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
0
19
0
9
Order By: Relevance
“…The total number of athletes was about 333 males and females, aged between 17 and 40 years, who practiced different sports (running, cycling, swimming, canoeing, athletics, skating, volleyball, football, basketball, rugby, and triathlon). For the sample characterization, seven studies used the VO 2 as a physiological measure, seven studies reported the length of time that the athletes had practiced the sport (over 2 years), and eight studies selected athletes participating in national, regional, or international competitions . No study reported the athlete's training phase during the course of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of athletes was about 333 males and females, aged between 17 and 40 years, who practiced different sports (running, cycling, swimming, canoeing, athletics, skating, volleyball, football, basketball, rugby, and triathlon). For the sample characterization, seven studies used the VO 2 as a physiological measure, seven studies reported the length of time that the athletes had practiced the sport (over 2 years), and eight studies selected athletes participating in national, regional, or international competitions . No study reported the athlete's training phase during the course of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The HRV data were provided by articles or by e‐mail through contact with the authors. Missing values are due to graphic representations in the articles and mismatched data received by e‐mail .…”
Section: Methodsmentioning
confidence: 99%
“…The basic physiological data, blood pressure and HR (HR baseline ) were measured after 10 minutes in the supine position according to a protocol standardized in our laboratory 18 . All measures were performed in a quiet, clinical laboratory room at controlled ambient temperature (21-24ºC).…”
Section: Participantsmentioning
confidence: 99%
“…Chronic, mechanical stretching of the sino-atrial node [2][3][4], changes in ionic concentration within the sino-atrial node [7], and localised changes in myocardial conduction [8] appear to play a role in the development of EIB. The current work of Molina [1] adds to that of others previously and further highlights the necessity to examine sino-atrial function as a key mechanism for EIB.…”
mentioning
confidence: 62%
“…
The recent cross-sectional comparison by Molina et al [1] highlights again the growing evidence for a reduced, cardiac intrinsic rate responsible for exercise-induced bradycardia (EIB). Several longitudinal studies [2][3][4] have previously shown EIB without alterations in cardiac autonomic modulation as evidenced by heart rate variability (HRV).
…”
mentioning
confidence: 99%